In vitro effects of palmitoleic acid on osteoblast differentiation in MG-63 osteosarcoma cells and human adipose-derived stromal cells - Coetzee, Magdalena (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2020.